MAMÁ, NO QUIERO MAS: LOOKING AHEAD IN THE REMEDIATION OF FEEDING DISORDERS IN HISPANIC INFANTS - Frigerio, Ailema Fernandez (European Scientific Journal, ESJ, 2014)
Disorders in infancy and early childhood are now understood to be complex and involve the factors of maturation, attachment, and family environment (Zero to Three, 2007). Feeding disorders in these developmental stages have a higher level of complexity, incorporating cultural factors as well. The failure to thrive resulting from these disorders eventually leads to both physical and cognitive decline in children (Chatoor, Surles et al., 2004). Research has consistently shown that a multidisciplinary treatment approach, with the family being central in the process of treatment, results in improved outcomes for children (Chatoor et al., 1992; Greer, Gulotta, Masler, & Laud, 2008; Piazza & Addison, 2007). Despite successes in the treatment of infant feeding disorders, Hispanics have disparities in finding culturally competent providers who speak Spanish and are intimately aware of cultural family dynamics (Flores, Olson, & Tomany-Korman, 2005; Howell & McFeeters, 2008; Malgady & Zayas, 2001). Additionally, Hispanic families have differing parenting styles when in a feeding situations than when in typical social settings (Cardona, Nicholson, & Fox, 2000). With these significant disparities existing in the delivery of services and the particular characteristics exhibited by Hispanic families in feeding situations, the need for programs that treat infant feeding disorders within a cultural context is imperative.